The prevalence and factors associated with sarcopenia in Thai older adults: A systematic review and meta-analysis - Phatcharaphon Whaikid; Noppawan Piaseu (Elsevier, 2024)
Objective: This systematic review and meta-analysis aimed to assess the prevalence and identify factors associated with sarcopenia in older Thais. Methods: Research studies were searched in online databases, including PubMed, Embase, Scopus, and Thai-Journal Citation Index. The articles included in this review were limited to being published between January 1, 2013 and January 31, 2023 and observational study designs. The research quality was evaluated using the Joanna Briggs Institute (JBI) critical appraisal tool for prevalence studies. A meta-analysis was performed using the JBI SUMARI software. The review protocol has been registered on PROSPERO with the assigned ID CRD42023420514. Results: A total of 265 research articles were initially identified, out of which 17 articles were included in this study, including a total of 4,668 participants aged 60 years and over, consisting of 1,380 (29.6%) men and 3,288 (70.4%) women. The overall prevalence of sarcopenia in Thai older adults was 20.7% (95% CI 14.4%-27.8%). Subgroup analysis of the sarcopenia prevalence based on the study areas revealed that the prevalence was 33.4% (95% CI 28.7%-38.3%) in hospitalized individuals, 23.2% (95% CI 12.5%-35.9%) in outpatient clinic settings, and 17.3% (95% CI 9.4%-26.8%) in community-living older adults. Advanced age (OR = 4.60, 95% CI 3.07-6.91), being male (OR = 2.30, 95% CI 1.37-3.85), low body mass index (BMI) (OR = 8.95, 95% CI 6.05-13.25), and malnutrition (OR = 2.78, 95% CI 2.09-3.70) are strong predictors of sarcopenia in older adults in Thailand. Conclusions: This systematic review represents the first assessment of the overall prevalence and factors associated with sarcopenia in Thai older adults, indicating its significant concern within this population. These findings are of importance for public health management aimed at preventing and managing sarcopenia in the country.